2021
DOI: 10.1186/s12967-021-02880-9
|View full text |Cite
|
Sign up to set email alerts
|

Mir-139-5p inhibits glioma cell proliferation and progression by targeting GABRA1

Abstract: Glioma is an extremely aggressive malignant neoplasm of the central nervous system. MicroRNA (miRNA) are known to bind to specific target mRNA to regulate post-transcriptional gene expression and are, therefore, currently regarded as promising biomarkers for glioma diagnosis and prognosis. The aim of the present study was to examine the pathogenesis and potential molecular markers of glioma by comparing the differential expression of miRNA and mRNA between glioma tissue and peritumor brain tissue. We explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 33 publications
(36 reference statements)
1
22
0
Order By: Relevance
“…we found some miRNAs acted as anti-oncogene in glioma patients (3). In a subsequent study, we have validated that miRNA-139-5p, miRNA-138-5p and miRNA-338-3p were anti-tumor factors (3)(4)(5). Another miRNA, identi ed in this study, is miRNA-383-5p, which could also be a potential therapeutic target and prognosis biomarker in glioma.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…we found some miRNAs acted as anti-oncogene in glioma patients (3). In a subsequent study, we have validated that miRNA-139-5p, miRNA-138-5p and miRNA-338-3p were anti-tumor factors (3)(4)(5). Another miRNA, identi ed in this study, is miRNA-383-5p, which could also be a potential therapeutic target and prognosis biomarker in glioma.…”
Section: Introductionsupporting
confidence: 62%
“…In previous studies, we identi ed nine glioma-associated miRNAs though bioinformatics tools. we found some miRNAs acted as anti-oncogene in glioma patients (3). In a subsequent study, we have validated that miRNA-139-5p, miRNA-138-5p and miRNA-338-3p were anti-tumor factors (3)(4)(5).…”
Section: Introductionmentioning
confidence: 54%
“…It has been shown that overexpression of miR-139-5p in vitro leads to the inhibition of cell proliferation, migration and invasion of glioma by targeting gamma-aminobutyric acid A receptor alpha 1 (GABRA1). Moreover, a correlation was found between the level of this miRNA, the probability of survival and the World Health Organization grade [ 71 ]. MiR-148a-3p is considered to be a tumor suppressor that is significantly reduced in several types of cancer, such as ovarian cancer, and gastric cancer [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs), small non-coding RNAs, are abundant classes of post-transcriptional regulators with the length of 20–24 nucleotides that are involved in the control of a broad range of cellular activities, such as cell proliferation [ 22 ], differentiation [ 23 ], apoptosis [ 24 ], and metabolism [ 25 ], and play a role in the replication and propagation of viruses [ 26 , 27 ]. The nucleotides 2–7 of the miRNA 5′ end, which is called the seed-sequence, usually target the 3′ untranslated region (3′-UTR), 5′ untranslated region (5′-UTR), or the coding sequence (CDS) of mRNAs either fully or partially to degrade mRNA or inhibit translation [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%